Nuclear Weapons in Regional Contexts: The Cases of Argentina and Brazil - Freire Jr., Olival (2015)
South America is a region which is free from nuclear weapons. However, this was not an inevitable development from the relationships among its countries. Indeed, regional rivalries between Brazil and Argentina, with military implications for both countries, lasted a long time. After wwii these countries took part in the race to obtain nuclear technologies and nuclear ambitions were part of the game. In the mid 1980s, the end of military dictatorships and the successful establishing of democratic institutions put an end to the race. Thus regional and national interests in addition to the establishment of democracies in Latin America have been responsible for the building of trust between the two countries. Meaningful international initiatives are once again needed in the framework of worldwide cooperation. This cooperation is better developed when democratic regimes are in place.